2004
DOI: 10.1258/095646204774195191
|View full text |Cite
|
Sign up to set email alerts
|

Genital syndromes and syndromic management of vaginal discharge in a community setting

Abstract: The objective of the study was to determine the community prevalence of genital syndromes in women and evaluate the syndromic management of vaginal discharge in this setting. A representative sample for the state of Tamilnadu was chosen using probability proportional to size cluster technique. Thirty clusters were selected from three districts. Demographic, sexual behaviour, risk factors, clinical and laboratory data were collected from the selected population using a structured questionnaire. Direct smear exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 10 publications
4
19
0
4
Order By: Relevance
“…13,14 These prevalence rates are much lower than those reported in Africa and Central America, 2 although, as in many other studies, we found chlamydia infection rates to be higher in younger women (4.3% in women aged <30 years vs.…”
supporting
confidence: 63%
“…13,14 These prevalence rates are much lower than those reported in Africa and Central America, 2 although, as in many other studies, we found chlamydia infection rates to be higher in younger women (4.3% in women aged <30 years vs.…”
supporting
confidence: 63%
“…This may be due to the low sensitivity and/or low specificity of some STI-associated symptoms 18. Furthermore, women tend to be more interested in their health, to pay more attention to symptoms, and subsequently to report them more often 19 20.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, asymptomatic STI, especially C trachomatis and N gonorrhoeae, are common 26. In addition, BV is commonly asymptomatic,27 overdiagnosed28 and overtreated,29 which could contribute to the increased risks of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%